Melatonin supplementation improves psychomotor and physical performance in collegiate student-athletes following a sleep deprivation night - Paryab, N.; Taheri, M.; H`Mida, C.; Irandoust, K.; Mirmoezzi, M.; Trabelsi, K.; Ammar, A.; Chtourou, H. (Chronobiology International, 2021)
Several studies report sleep deprivation negatively impacts post-cognitive and physical performance, and other functions. Recent findings indicate ingestion of melatonin prior to exercise enhances tolerance to training and improves competition. We investigated the effects of melatonin supplementation on psychomotor performance and selected physical fitness measures of collegiate student-athletes following 4 h and 24 h of sleep deprivation. The study employed a repeated-measures, double-blind, randomized controlled protocol with posttest control group design with six conditions [3 sleep conditions (without sleep deprivation, 4 h sleep deprivation (4SD) and 24 h sleep deprivation (24SD)) × 2 supplementation conditions (melatonin and placebo)]. Ten trained male collegiate student-athletes (mean ± SD; age: 20 ± 2 y) attended the laboratory on six occasions with 72 h between successive visits. Placebo or 6 mg of melatonin were administered orally in capsules 30 min before the tests of: static and dynamic balance, reaction time, and anaerobic power. Also, blood lactate was measured before and 3 min after the anaerobic power exercise. During the placebo session, the results indicated that 4SD and 24SD had negative effect on the measured parameters, with higher impacts of the 24SD condition. Compared to placebo and during both 4SD and 24SD conditions, melatonin had a positive effect on static and dynamic balance, anaerobic power, blood lactic acid, and reaction time (p < .05). However, 6 mg melatonin ingestion had no significant effect on all dependent variables in collegiate student-athletes after the night without a sleep deprivation (p > .05). In conclusion, 6 mg of melatonin may be used by student-athletes to improve balance and psychomotor and physical performances after 4 h or 24 h of sleep deprivation.